1994
DOI: 10.1007/bf00571954
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring of blood glucose in overweight type 2 diabetic patients

Abstract: Self-monitoring of blood glucose (SBGM) is widely recommended for both type 1 and type 2 diabetic patients despite the lack of evidence of benefit in glucose control or as an aid in weight loss in type 2 subjects. This study tested the hypothesis that combined use of SMBG and dietary carbohydrate (CHO) counting, using the blood monitoring results to shape dietary CHO quotas, is beneficial in managing type 2 diabetes. Twenty-three overweight (body mass index, BMI 27.5-44 kg/m2) patients aged 40-75 participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 14 publications
3
98
0
2
Order By: Relevance
“…At the end of this study, subjects who practiced more frequent meal related SMBG reduced their carbohydrate intake (p = 0.04). Similar findings have been reported in previous studies [80,81]. Furthermore, it was also explained that persistent fasting hyperglycaemia might be due to medication non-adherence and wrong timing of medication intake.…”
Section: Self-monitoring Blood Glucose Practicessupporting
confidence: 90%
“…At the end of this study, subjects who practiced more frequent meal related SMBG reduced their carbohydrate intake (p = 0.04). Similar findings have been reported in previous studies [80,81]. Furthermore, it was also explained that persistent fasting hyperglycaemia might be due to medication non-adherence and wrong timing of medication intake.…”
Section: Self-monitoring Blood Glucose Practicessupporting
confidence: 90%
“…Our systematic review 11 identified 7 randomized controlled trials, [29][30][31][32][33][34][35] enrolling a total of 2270 patients with type 2 diabetes managed with oral antidiabetes agents or lifestyle measures alone. These trials compared self-monitoring of blood glucose with no self-monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…The benefit of SMBG may be further increased by better integrating SMBG practice into an overall program of health education (promoting patientlevel behavioral modifications in res p o n s e t o S M B G r e a d i n g s ) a n d therapeutic decision making (22)(23)(24)(25)(26). Research is needed to develop specific clinical guidelines for patients regarding optimal timing and frequency of SMBG initiation and practice maintenance and to help clinicians better integrate patient's SMBG records into the therapeutic decision-making process.…”
Section: Karter and Associatesmentioning
confidence: 99%